2013
DOI: 10.11607/ijp.3008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Spray Pattern, Water Flow Rate, and Cutting Position on the Cutting Efficiency of High-Speed Dental Handpieces

Abstract: This assignment applies to all translations of the Work as well as to preliminary display/posting of the abstract of the accepted article in electronic form before publication. If any changes in authorship (order, deletions, or additions) occur after the manuscript is submitted, agreement by all authors for such changes must be on file with the Publisher. An author's name may be removed only at his/her written request. (Note: Material prepared by employees of the US government in the course of their official d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Reduced cutting efficiency and debris clogging result in concentration of frictional heat which in turn leads to an increase in pulpal temperature [5]. One study found an improvement in cutting efficiency with 3- and 4- ports while making groove cuts [15], while other studies found no significance [16]. This may be due to the different arrangements of the coolant port and bur, which consequently impacted coolant accessibility to the surface.…”
Section: Introductionmentioning
confidence: 99%
“…Reduced cutting efficiency and debris clogging result in concentration of frictional heat which in turn leads to an increase in pulpal temperature [5]. One study found an improvement in cutting efficiency with 3- and 4- ports while making groove cuts [15], while other studies found no significance [16]. This may be due to the different arrangements of the coolant port and bur, which consequently impacted coolant accessibility to the surface.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, dental handpieces with a multiport coolant design exhibit greater cutting efficiency compared to those with a single coolant port, even if the 1-port handpiece has a higher coolant flow rate. 15,16 The difference in remaining dentine thickness between cuts may have also influenced the results, despite this factor being minimized through the selection of teeth with similar morphology, and standardization of the bur type, size, cavity preparation length, and distance from the center of the tooth, as well as using each tooth as the control for each preparation. In addition, other factors that have not been intensely studied, such as the size of the coolant port aperture and the speed of the water coolant, could have influenced the cooling efficiency during drilling and contributed to the observed findings.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, and as advertised by numerous dental manufacturers without any scientific validation, handpieces containing a greater number of coolant ports display greater cooling efficiency due to the wider distribution of the coolant over the cutting surfaces. In addition, dental handpieces with a multiport coolant design exhibit greater cutting efficiency compared to those with a single coolant port, even if the 1‐port handpiece has a higher coolant flow rate 15,16 . The difference in remaining dentine thickness between cuts may have also influenced the results, despite this factor being minimized through the selection of teeth with similar morphology, and standardization of the bur type, size, cavity preparation length, and distance from the center of the tooth, as well as using each tooth as the control for each preparation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is well known that the heat produced during restorative procedures is a source of trauma for the dental pulp and has been suggested to lead to inflammation and necrosis [ 19 , 20 ]. This is because during tooth preparation a variable amount of heat is transmitted to the tooth, depending on the type of bur, cutting time, and rate, the pressure applied, the cooling technique, and the speed and torque of the rotary instrument [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%